2006
DOI: 10.1002/app.25301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impregnation with imersol‐AQUA on yellow color tone of some softwoods and varnishes

Abstract: This study has been performed for determining impacts of impregnation with Imersol-AQUA (I-AQUA) to yellow color tone of some softwoods and varnishes. For this purpose, samples of scotch pine (Pinus sylvestris L.), oriental spruce (Picea orientalis L.), and Uludag fir (Abies bornmlleriana L.) wood, prepared according to the ASTM D 358 standards, are impregnated with I-AQUA by short-term (S), medium-term (M), and long-term (L) immersion techniques in accordance with ASTM D 1413 and producer's definition. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, the impregnation materials decreased the red color tone value in wood materials [38]. It is reported that the impregnation of some softwoods with some chemicals has increased the yellow color tone [39]. Baysal et al also reported that three color parameters ( * , * , and * ) of Scots pine decreased after the AD-KD5 impregnation process [40].…”
Section: Effect Of Natural Weathering On Color Stabilitymentioning
confidence: 99%
“…However, the impregnation materials decreased the red color tone value in wood materials [38]. It is reported that the impregnation of some softwoods with some chemicals has increased the yellow color tone [39]. Baysal et al also reported that three color parameters ( * , * , and * ) of Scots pine decreased after the AD-KD5 impregnation process [40].…”
Section: Effect Of Natural Weathering On Color Stabilitymentioning
confidence: 99%
“…Thus, the yellow color value is declared to be high in Scotch pine wood. 5 For samples varnished after impregnation, yellow tone value was the highest in Oriental spruce 1 Tc 1 Sp and the lowest in Oriental beech 1 Tc 1 Si after impregnation with Tc.…”
Section: Discussionmentioning
confidence: 98%
“…In a similar research, it was reported that Imersol Aqua treatment caused to an increase of the yellow color tone of some softwood types. 5 …”
Section: Yellow Color Changementioning
confidence: 97%
See 1 more Smart Citation
“…[15][16][17] Furthermore, the effects of impregnated substances on the brightness, color, hardness and burning of the varnish types have been investigated in many recent studies. [18][19][20][21][22] Sapele (Entandrophragma cylindricum) is a native species of Africa with a distribution ranging from the Ivory Coast to Cameroon and through Zaire to Uganda. Its heartwood is medium to fairly dark reddish brown or purple brown and its sapwood is pale yellow.…”
Section: Introductionmentioning
confidence: 99%